Effects of added Zn in diets with Ractopamine HCl on growth performance and carcass quality of finishing pigs in a commercial environment - C B Paulk; K J Prusa; Michael D Tokach; Jim L Nelssen; Joel M DeRouchey; Robert D Goodband; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2012)
The experiment was conducted in a commercial facility to determine the effects of added Zn on the performance of finishing pigs fed Ractopamine HCl (RAC; PayleanÂ®; Elanco Animal Health, Greenfield, IN). Pigs were randomly assigned to pens based on gender (14 barrow pens, 11 gilt pens, and 23 mixed-gender pens), with 25 to 28 pigs per pen. Previously, pens of pigs were assigned to treatments containing 0, 7.5, or 15% bakery by-product in a completely randomized design while balancing for initial BW and gender. On d 75, treatments were implemented to determine the effects of adding 50 ppm Zn from ZnO on finishing pig performance. A total of 1,234 pigs (PIC 337 × 1050; average BW 224.6 lb) were used in a 28-d study. Pens of pigs were randomly assigned to diets with and without 50 ppm added Zn from zinc oxide (ZnO) and balanced by BW, bakery by-product, and gender. All diets contained 5 ppm RAC and 83 ppm Zn from ZnO provided by the trace mineral premix. There were 24 pens per treatment. Overall (d 75 to 102), no differences (P>0.22) in growth performance or carcass characteristics were observed when pigs were fed diets with 50 ppm added Zn compared with the RAC control. For pigs subsampled on d 84, pigs fed diets with 50 ppm added Zn had decreased (P<0.05) edge belly thickness compared with pigs fed the control. For pigs subsampled on d 102, pigs fed diets with 50 ppm added Zn had decreased (P<0.02) backfat thickness, belly weight, and edge belly thickness; a tendency for decreased (P<0.07) middle belly thickness; and increased (P<0.01) percentage lean compared with pigs fed the RAC control. In contrast with our previous research, these data indicate that adding 50 ppm Zn from ZnO to finishing pig diets containing RAC did not improve overall performance. Consistent with the earlier research, income over feed cost (IOFC) was numerically increased with the addition of Zn.; Swine Day, Manhattan, KS, November 15, 2012
Keywords: Kansas Agricultural Experiment Station contribution; no. 13-026-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1074; Swine; Finishing pig; Ractopamine HCl; Zinc